Mirʼāt al-quds : a life of Christ for Emperor Akbar : a commentary on Father Jerome Xavier's text and the miniatures of Cleveland Museum of Art, Acc. no. 2005.145 - Carvalho, Pedro de Moura (Studies and sources in Islamic art and architecture ;, 2012)
Akbar's commission of a Life of Christ from the Jesuit Jerome Xavier resulted in a fascinating text (1602) in which the author's concern not to antagonize his Muslim hosts is apparent. The 27 miniatures were inspired by the text itself, resulting in unique interpretations of episodes that often do not find parallels in a European context.